A semiconductor / molybdenum-based acidic composite catalyst and its application in preparation of dihydroquinazolinone derivatives

CN121892211BActive Publication Date: 2026-10-30CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610271631.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-06
Publication Date
2026-10-30
Estimated Expiration
2046-03-06

AI Technical Summary

Technical Problem

然而,现有催化体系包括均相催化体系、贵金属催化体系与强酸催化体系等,分别存在以下问题,制约了该反应工业化应用:

Benefits of technology

(1)本发明将钼基组分固有的酸性活性位点与半导体材料的特性相结合,不仅有效保持了必要的催化酸性,更通过界面间的相互作用显著提升了整体的催化效率与稳定性,从而克服了单一组分材料的局限性,有利于实现高效、可循环的酸催化合成过程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121892211B_ABST
    Figure CN121892211B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of organic synthesis and photocatalysis, and relates to a semiconductor / molybdenum-based acidic composite catalyst and application thereof in preparation of dihydroquinazolinone derivatives. The composite catalyst comprises a semiconductor material and a molybdenum-based acidic component loaded on the surface and inside of the semiconductor material, and a heterojunction structure is formed between the semiconductor material and the molybdenum-based acidic component; the semiconductor material comprises titanium dioxide, and the molybdenum-based acidic component is one or more of ammonium molybdate tetrahydrate, ammonium molybdate dihydrate, potassium molybdate, phosphomolybdate, silicomolybdate, ammonium molybdophosphate, molybdenum trioxide and molybdenum dioxide. The application forms a stable interface structure in a loading mode, keeps the acidic active sites, and realizes synergistic enhancement of the catalytic effect by means of the interface electron regulation capacity of the semiconductor material. The system not only significantly improves the reaction efficiency, but also has good cycle stability and recyclability, thereby providing a new technical path for green and efficient synthesis of dihydroquinazolinone compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic synthesis and photocatalysis technology, specifically relating to a semiconductor / molybdenum-based acidic composite catalyst and its application in the preparation of dihydroquinazolinone derivatives. Background Technology

[0002] Dihydroquinazolinones (2,3-dihydroquinazolin-4(1H)-one) are important nitrogen-containing fused heterocyclic structures, widely found in various natural products and synthetic molecules with significant biological activity. They are key structural units for developing antitumor, anti-inflammatory, and antiviral drugs and functional molecules. Efficient and green synthetic methods for these compounds have attracted considerable attention. Currently, the mainstream synthetic route is the condensation cyclization reaction of o-aminobenzamide with aldehydes (or alcohols). However, existing catalytic systems, including homogeneous catalytic systems, noble metal catalytic systems, and strong acid catalytic systems, each have the following problems that restrict the industrial application of this reaction:

[0003] (1) Homogeneous catalytic systems: difficult to separate and recover, poor cycling stability. For example, the chiral phosphoric acid catalytic system reported by Tang et al. (Org. Lett. 2022, 24, 7955–7960) exhibits high enantioselectivity in asymmetric synthesis, but catalyst separation is difficult, recovery costs are high, and the activity decreases significantly during reuse, making recycling difficult. Similar chiral phosphoric acid catalytic systems (such as Huang et al., ACS Catal. 2013, 3, 2244–2247) are also limited by the inherent bottlenecks of homogeneous catalysis, facing challenges of product purification and catalyst loss in industrial scale-up.

[0004] (2) Noble metal catalytic systems: These systems are costly and pose resource and environmental risks. To improve separability, some research has shifted to heterogeneous catalysis, but these often rely on noble metal catalysts such as Pt and Pd (e.g., Siddiki et al., Catal. Sci. Technol. 2014, 4, 1716–1719; Hikawa et al., J. Org. Chem. 2012, 77, 7046–7051). Although these systems have high activity, the catalysts are expensive, metal resources are scarce, and there may be risks of metal residues in fields such as drug synthesis, which contradicts the principles of green chemistry and sustainable development.

[0005] (3) Strong acid catalytic system: equipment corrosion risks and environmental burden. Some heterogeneous systems use strong acid or sulfonic acid functionalized materials (such as Yadav et al., New J. Chem. 2021, 45, 15928–15941), which solves some separation problems, but the strong acid environment is corrosive to the reaction equipment and may bring environmental burden in post-processing and waste discharge, limiting its safe application in industrial production.

[0006] In addition, many existing catalytic systems (including some heterogeneous catalysts) require higher reaction temperatures (such as Ghorbani-Choghamarani et al., Appl. Organomet. Chem. 2015, 29, 707–711) or longer reaction times to achieve ideal yields, resulting in higher overall energy consumption and lower production efficiency, which is not conducive to the industrial demand for energy conservation and emission reduction. Summary of the Invention

[0007] The purpose of this invention is to provide a semiconductor / molybdenum-based acidic composite catalyst and its application in the preparation of dihydroquinazolinone derivatives, thereby overcoming the shortcomings of existing technologies. By forming a stable interfacial structure through a supported method, it maintains the acidic active sites while leveraging the interfacial electronic modulation capabilities of semiconductor materials to achieve synergistic enhancement of the catalytic effect. This system not only significantly improves reaction efficiency but also exhibits good cycle stability and recyclability, thus providing a new technical route for the green and efficient synthesis of dihydroquinazolinone compounds.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a semiconductor / molybdenum-based acidic composite catalyst, comprising a semiconductor material and a molybdenum-based acidic component supported on its surface and internally; wherein a heterojunction structure is formed between the semiconductor material and the molybdenum-based acidic component; The semiconductor material is selected from titanium dioxide, zinc oxide, zirconium oxide, aluminum oxide, tin oxide, tungsten trioxide, or graphitic carbon nitride; The molybdenum-based acidic components are one or more of the following: ammonium molybdate, potassium molybdate, phosphomolybdic acid, silicomolybdic acid, ammonium salts of molybdenum-phosphopolyacids, compounds containing molybdenum-oxygen cluster structures, molybdenum trioxide, and molybdenum dioxide.

[0009] This invention constructs a composite structure of a semiconductor and a molybdenum-based component, generating a strong synergistic effect at the interface between the two. By combining the inherent acidic active sites of the molybdenum-based component with the characteristics of the semiconductor material, not only is the necessary catalytic acidity effectively maintained, but the overall catalytic efficiency and stability are also significantly improved through interfacial interactions. This overcomes the limitations of single-component materials and facilitates efficient and recyclable acid-catalyzed synthesis processes.

[0010] In some other embodiments, the loading of the molybdenum-based acidic component is 1-30 wt%.

[0011] Preferably, the semiconductor material is titanium dioxide, which can be anatase, rutile, or a mixture thereof, with a specific surface area of ​​20–300 m². 2 / g, with a pore size of 2–50 nm; The molybdenum-based acidic component is phosphomolybdic acid. Compounds containing molybdenum-oxygen cluster structures include one or more of aluminum molybdic acid, iron molybdic acid, and cobalt molybdic acid.

[0012] The loading of the molybdenum-based acidic component is 10-20 wt%. This loading achieves the best balance between ensuring catalytic activity and maintaining structural stability. It provides a sufficient number of acidic centers to drive the condensation cyclization reaction while ensuring that the molybdenum-based component is highly dispersed and forms a sufficient and close interfacial contact with the semiconductor support, thereby maximizing the interfacial synergistic effect and obtaining a highly active and stable composite catalytic material.

[0013] In some other embodiments, the semiconductor / molybdenum-based acidic composite catalyst exhibits photocatalytic activity under visible light at wavelengths of 420–450 nm.

[0014] This composite catalyst can be effectively excited and generate active species under visible light irradiation at wavelengths of 420–450 nm. This creates a novel photo / acid synergistic catalytic reaction system for the synthesis of dihydroquinazolinone derivatives. The reaction no longer depends solely on the traditional thermocatalytic acid center. The introduction of visible light can activate reactant molecules or intermediates, effectively reducing the activation energy of the reaction, thereby further improving the reaction rate and conversion efficiency under mild conditions.

[0015] In a second aspect, the present invention provides a method for preparing the semiconductor / molybdenum-based acidic composite catalyst described in the first aspect, comprising the following steps: Semiconductor materials are added to a solvent to form a suspension, molybdenum-based acidic components are added to the suspension and stirred to mix, and then reacted by hydrothermal method. After the reaction is completed, the semiconductor / molybdenum-based acidic composite catalyst is obtained by drying. The hydrothermal reaction temperature is 120–150℃, and the reaction time is 6–24 h.

[0016] This invention employs a hydrothermal method to precisely control and achieve uniform distribution and stable loading of molybdenum-based acidic components on the surface of semiconductor materials. The hydrothermal method utilizes a high-temperature, high-pressure, closed reaction environment, which promotes high dispersion of the active components while more effectively driving interfacial reconstruction and chemical bonding, thereby forming a more stable and tightly bound composite system. This improves the stability and reusability of the catalyst. It avoids problems such as component inhomogeneity and poor interfacial contact that may result from simple physical mixing, and can construct composite structures with strong interfacial synergistic effects.

[0017] In some other embodiments, the solvent is one or both of water and alcohol, and the mixing temperature is room temperature for 1-4 hours.

[0018] The semiconductor material is preferably titanium dioxide, the molybdenum-based acidic component is preferably phosphomolybdic acid, and the solvent is selected from deionized water, ethanol, or a mixture of water and alcohol.

[0019] In some other embodiments, the drying temperature is 80–120°C and the time is 6–12 h.

[0020] Thirdly, the present invention provides the application of the semiconductor / molybdenum-based acidic composite catalyst described in the first aspect in dihydroquinazolinone derivatives, characterized in that the general structural formula of the dihydroquinazolinone derivatives is as follows: ; wherein R is selected from alkyl, substituted alkyl, aryl and substituted aryl, wherein the substituent of the substituted alkyl or substituted aryl is selected from halogen, amino, alkoxy and thiophene. Preferably, R is selected from halogen-substituted aryl, amino-substituted aryl, nitro-substituted aryl, cycloalkyl, alkoxy-substituted aryl, and thiophene-substituted aryl, with the substitution position being the 4th or 6th position of the aryl group.

[0021] More preferably, R is selected from halogen-substituted benzene rings, amino-substituted benzene rings, nitro-substituted benzene rings, cycloalkyl, alkoxy-substituted benzene rings, and thiophene-substituted benzene rings, and the halogen is F, Cl, Br, and I.

[0022] Fourthly, the present invention provides a method for preparing a dihydroquinazolinone derivative, wherein, in the presence of the semiconductor / molybdenum-based acidic composite catalyst described in the first aspect, anthranilamide and aldehyde-ketone compounds undergo a condensation cyclization reaction to obtain the dihydroquinazolinone derivative. Aldehydes and ketones include one or more of p-fluorobenzaldehyde, dimethylaminobenzaldehyde, p-nitrobenzaldehyde, cyclohexanone, 4-methoxybenzaldehyde, and 2-thiophenecarboxaldehyde.

[0023] This invention utilizes a semiconductor / molybdenum-based acidic composite catalyst to efficiently catalyze a one-pot condensation cyclization reaction of o-aminobenzamide with various aldehydes and ketones. This method has broad substrate applicability, readily reacting with aromatic aldehydes (such as p-fluorobenzaldehyde, p-nitrobenzaldehyde, 4-methoxybenzaldehyde, and 2-thiophenecarboxaldehyde), as well as aliphatic aldehydes and ketones (such as cyclohexanone). It also reacts efficiently with aromatic aldehydes containing strong electron-donating or electron-withdrawing groups (such as dimethylaminobenzaldehyde and p-nitrobenzaldehyde). This fully demonstrates that the composite catalyst possesses excellent acid catalytic activity and good functional group tolerance, making it suitable for substrates with different electronic effects and steric hindrances. It provides a general and concise synthetic method for efficiently and selectively constructing a diverse library of dihydroquinazolinone compounds.

[0024] Specifically, the aldehyde-ketone substrate is first dissolved in an organic solvent, and then an equal amount of o-aminobenzamide is added to carry out the reaction; the organic solvent is selected from one or more of toluene, DMF, DMA, acetonitrile, tetrahydrofuran, pyridine, methanol, anhydrous ethanol, dichloromethane, dichloroethane, ethyl acetate, and ethyl formate.

[0025] In some other embodiments, the condensation cyclization reaction is carried out under visible light irradiation at a wavelength of 420–450 nm at 20–80°C for 3–5 h. Preferably, the reaction is carried out at 25°C for 4 h.

[0026] This condensation cyclization reaction can be efficiently completed in just 3-5 hours under relatively mild temperatures (20-80°C) and visible light irradiation at 420-450 nm. The ingenious combination of light and heat energy provides a dual driving force; the introduction of visible light excites the semiconductor / molybdenum-based acidic composite catalyst, generating active species to activate reactants or intermediates. This effectively reduces the activation energy and significantly improves the reaction rate and atom economy without the need for high temperatures, high pressures, or highly corrosive catalysts. Compared to many traditional synthetic methods that require high temperatures, long durations, or inert atmospheres, the reaction conditions provided by this invention not only significantly reduce energy consumption but also offer simpler and safer operation, demonstrating a clear advantage in the development of environmentally friendly and sustainable organic synthesis processes.

[0027] In some other embodiments, after the reaction is complete, the product is further subjected to concentration, extraction, drying, and column chromatography.

[0028] Specifically, the extractant used in the extraction is selected from one or more of DMF, DMA, acetonitrile, tetrahydrofuran, pyridine, methanol, anhydrous ethanol, dichloromethane, dichloroethane, ethyl acetate, and ethyl formate. Anhydrous sodium sulfate was used for drying; The eluent for column chromatography is a petroleum ether / ethyl acetate elution system with a volume ratio of 9:1 to 5:1.

[0029] The solid obtained after filtration is dried, then soaked in a solvent and dried again to obtain a reusable photocatalyst; the solvent is selected from one or more of methanol, water, and DMF.

[0030] The beneficial effects of this invention are: (1) This invention combines the inherent acidic active sites of molybdenum-based components with the characteristics of semiconductor materials, which not only effectively maintains the necessary catalytic acidity, but also significantly improves the overall catalytic efficiency and stability through the interaction between interfaces, thereby overcoming the limitations of single-component materials and facilitating the realization of efficient and recyclable acid-catalyzed synthesis processes.

[0031] (2) This invention employs either the impregnation method or the hydrothermal method, two solution chemical synthesis methods, which can precisely control and achieve uniform distribution and stable loading of molybdenum-based acidic components on the surface of semiconductor materials. This avoids problems such as component inhomogeneity and poor interfacial contact that may result from simple physical mixing, and can construct a composite structure with strong interfacial synergistic effects. This is the fundamental guarantee for obtaining high catalytic efficiency, excellent stability, and good recyclability.

[0032] (3) This invention utilizes a composite catalyst that can be excited under visible light irradiation to generate photogenerated charge carriers, which synergistically interact with acidic sites to significantly improve the yield efficiency of dihydroquinazolinone derivatives under mild conditions. Simultaneously, this composite catalyst is a solid heterogeneous material, which can be separated from the reaction system through simple filtration or centrifugation, greatly simplifying the post-processing procedure and facilitating catalyst recycling, thus solving the problem of difficult recovery of homogeneous acid catalysts. Furthermore, this method has broad substrate applicability, exhibiting good compatibility with various aromatic aldehydes and aliphatic aldehydes and ketones, including those with electron-donating, electron-withdrawing, and heterocyclic groups, providing a universal and efficient synthetic platform for constructing a diverse library of dihydroquinazolinone compounds. Attached Figure Description

[0033] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0034] Figure 1 The images shown are TEM and SEM images of titanium dioxide and phosphomolybdic acid in Example 1 of the present invention. Among them, a is an SEM image with a scale bar of 500 nm, b is a TEM image with a scale bar of 20 nm, c is an HRTEM image with a scale bar of 5 nm, and d is a comparative XRD image of titanium dioxide and titanium dioxide-phosphomolybdic acid.

[0035] Figure 2 This is the UV absorption spectrum of titanium dioxide and phosphomolybdic acid in Example 1 of the present invention; Figure 3 The diagrams show the impedance and photocurrent comparison of titanium dioxide and titanium dioxide-phosphomolybdic acid in Example 1 of the present invention, where a is the impedance diagram and b is the photocurrent diagram. Figure 4 The NMR spectrum of 2-(4-fluorophenyl)-2,3-dihydro-4(1H)-quinazolinone, the product corresponding to p-fluorobenzaldehyde in Example 1 of this invention; Figure 5 The NMR spectrum of the substrate dimethylaminobenzaldehyde in Example 2 of this invention is 2-[4-(dimethylamino)phenyl]-2,3-dihydro-4(1H)-quinazolinone. Figure 6 The NMR spectrum of the substrate p-nitrobenzaldehyde in Example 2 of this invention is 2,3-dihydro-2-(4-nitrophenyl)-4(1H)-quinazolinone. Figure 7 The NMR spectrum of the substrate cyclohexanone in Example 2 of this invention is 2-cyclohexyl-2,3-dihydro-4(1H)-quinazolinone. Figure 8 This is the NMR spectrum of 4-methoxybenzaldehyde and 2,3-dihydro-2-(4-methoxyphenyl)-4(1H)-quinazolinone in Example 2 of the present invention; Figure 9 This is the NMR spectrum of 2,3-dihydro-2-(2-thienyl)-4(1H)-quinazolinone, in Example 2 of the present invention, where the substrate is 2-thiophenebenzaldehyde and the product is 2,3-dihydro-2-(2-thiophene)-4(1H)-quinazolinone. in, Figures 4-9 The blue text above the image is information provided by the spectral analysis software; even if the numerical values ​​are unclear, it does not affect the structure of the corresponding product. Detailed Implementation

[0036] Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention. Specific conditions not specified in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Components whose manufacturers are not specified are all commercially available conventional products.

[0037] As mentioned earlier, existing catalytic systems in the synthesis of dihydroquinazolinone generally face common problems such as difficulty in separating homogeneous catalysts and poor recyclability, high cost and insufficient environmental friendliness of precious metal catalysts, corrosion and pollution risks in strong acid systems, and harsh reaction conditions and high energy consumption.

[0038] To address the aforementioned technical problems, this invention proposes a novel semiconductor / molybdenum-based acidic composite catalytic system. This system, by constructing a stable supported interface structure, retains the acidic catalytic sites while leveraging the electronic modulation capabilities of the semiconductor material to achieve synergistically enhanced catalytic effects. It not only efficiently catalyzes the condensation cyclization reaction of o-aminobenzamide with aldehydes under mild conditions but also exhibits excellent recyclability and cycle stability, thus providing a new, industrially promising approach for the green and efficient synthesis of dihydroquinazolinone compounds.

[0039] Example 1 This example uses the synthesis of 2-(4-fluorophenyl)-2,3-dihydro-4(1H)-quinazolinone as an example to illustrate the catalyst used in its synthesis and the catalytic synthesis reaction: (1) Preparation of semiconductor / molybdenum-based acidic composite catalyst: 1.0 g of titanium dioxide (TiO2) was weighed and dispersed in 50 mL of deionized water, and ultrasonically dispersed for 30 min to prepare a TiO2 suspension. 0.10 g of phosphomolybdic acid (PMA) was weighed and dissolved in 10 mL of deionized water, and slowly added dropwise to the TiO2 suspension. The mixture was stirred at room temperature for 2 h. Subsequently, the solvent was evaporated by stirring in an 80℃ water bath to obtain a solid. The obtained solid was dried at 100℃ for 12 h, and after grinding, a semiconductor / molybdenum-based acidic composite catalyst (TiO2-PMA) was obtained.

[0040] Depend on Figure 1 As shown in (a), the TiO2 nanoparticles are uniformly dispersed at the micron scale, with regular particle morphology and no obvious agglomeration, indicating that the prepared TiO2 nanomaterials have good particle size uniformity and dispersibility.

[0041] Depend on Figure 1 As shown in (b), the TEM image at the nanoscale shows that PMA molecules are uniformly attached to the TiO2 surface and form a close contact interface with TiO2 nanoparticles, and a stable binary heterojunction structure may be constructed between them.

[0042] Depend on Figure 1 As shown in (c), the HRTEM image clearly shows the lattice arrangement of TiO2 and the continuous interface between TiO2 and PMA. The lattice at the interface remains intact and ordered, proving the formation of the TiO2-PMA heterojunction.

[0043] Depend on Figure 1 As shown in (d) of the XRD comparison diagram, the diffraction peak positions of TiO2 remain basically unchanged, indicating that the loading of PMA did not destroy the lattice structure of TiO2. PMA is modified on the TiO2 surface in the form of amorphous or microcrystalline material, forming a typical interface heterojunction.

[0044] Depend on Figure 2 As can be seen from the ultraviolet absorption diagram, the light absorption edge of the TiO2–PMA binary system shows a slight red shift and an enhanced absorption intensity, indicating that the formation of the heterojunction improves the light absorption capacity of the material, which is conducive to the generation of more photogenerated electron-hole pairs, thereby providing an effective light driving force for the photocatalytic reaction.

[0045] Depend on Figure 3 Electrochemical impedance spectroscopy shows that the interfacial charge transfer impedance of TiO2–PMA is lower than that of TiO2 alone, indicating that the heterojunction interface can effectively promote the migration of photogenerated electrons. Photocurrent response test shows that the photocurrent of the binary system is enhanced, further verifying that the TiO2–PMA heterojunction can improve the separation efficiency of photogenerated carriers, thereby improving photocatalytic activity.

[0046] (2) Preparation of dihydroquinazolinone derivatives: 1 mmol of o-aminobenzamide, 1 mmol of p-fluorobenzaldehyde, 5 mL of ethanol solvent, and 20 mg of the semiconductor / molybdenum-based acidic composite catalyst (PMA / TiO2) prepared in step (1) were added to a 25 mL round-bottom flask. The reaction was carried out under visible light LED irradiation (λ=420-450 nm). The reaction was magnetically stirred at 25 °C for 4 h. After the reaction was completed, the mixture was cooled, the catalyst was recovered by filtration, the solvent was evaporated under reduced pressure, and the filtrate was recrystallized from ethanol to obtain the target product. The yield of the product was 95%, and the purity was 99%.

[0047] The NMR spectrum of 2-(4-fluorophenyl)-2,3-dihydro-4(1H)-quinazolinone is shown below. Figure 4 As shown, its structural formula is as follows: .

[0048] Example 2 This example uses the synthesis of 2-[4-(dimethylamino)phenyl]-2,3-dihydro-4(1H)-quinazolinone as an example to illustrate the catalyst used in its synthesis and the catalytic synthesis reaction: (1) Preparation of semiconductor / molybdenum-based acidic composite catalyst: 2.0 g of titanium dioxide (TiO2) was weighed and dispersed in 50 mL of ethanol, and ultrasonically dispersed for 30 min to prepare a TiO2 suspension. 0.3 g of ammonium molybdate tetrahydrate (AMT) was weighed and dissolved in 10 mL of deionized water, and slowly added dropwise to the TiO2 suspension. The mixture was stirred at room temperature for 2 h. Subsequently, the reaction was carried out in a hydrothermal reactor at 150 °C for 12 h. After the reaction was complete, the resulting mixed solution was filtered, and the solid was vacuum dried at 60 °C for 12 h. After grinding, a semiconductor / molybdenum-based acidic composite catalyst (TiO2-AMT) was obtained.

[0049] (2) Preparation of dihydroquinazolinone derivatives Unlike the preparation of dihydroquinazolinone derivatives in step (2) of Example 1, p-fluorobenzaldehyde was replaced in equal amounts with p-dimethylaminobenzaldehyde, p-nitrobenzaldehyde, cyclohexanone, 4-methoxybenzaldehyde, and 2-thiophenealdehyde, respectively. The catalyst obtained in step (1) of Example 1 was replaced with the catalyst obtained in step (1) of Example 2, while other preparation conditions remained unchanged. The reaction was carried out under the same conditions for 4 h. The following products were obtained respectively. Specifically: ①The substrate is dimethylaminobenzaldehyde The corresponding product was 2-[4-(dimethylamino)phenyl]-2,3-dihydro-4(1H)-quinazolinone, with a yield of 98% and a purity of 99%; the NMR spectrum is shown below. Figure 5 As shown, its structural formula is as follows: .

[0050] ②The substrate is p-nitrobenzaldehyde The corresponding product was 2,3-dihydro-2-(4-nitrophenyl)-4(1H)-quinazolinone, with a yield of 96% and a purity of 98%; the NMR spectrum is shown below. Figure 6 As shown, its structural formula is as follows: ; 1 H NMR (500 MHz, DMSO- d 6) δ 8.75 (s, 1H), 8.45 – 8.34 (m, 2H), 8.27 –8.15 (m, 2H), 7.96 (s, 1H), 7.83 (dd, J = 7.7, 1.5 Hz, 1H), 7.69 – 7.51 (m,2H), 7.38 (td, J = 7.6, 1.2 Hz, 1H), 7.27 (dd, J= 7.9, 1.1 Hz, 1H). ③The substrate is cyclohexanone The corresponding product was 2-cyclohexyl-2,3-dihydro-4(1H)-quinazolinone, with a yield of 97% and a purity of 99%; the NMR spectrum is shown below. Figure 7 As shown, its structural formula is as follows: ; 1 H NMR (500 MHz, DMSO- d 6) δ 7.72 (s, 2H), 7.52 (s, 1H), 7.54 – 7.49 (m, 1H), 7.12 (ddd, J = 8.4, 7.0, 1.5 Hz, 2H), 7.08 – 7.04 (m, 2H), 6.66 (dd, J =8.3, 1.2 Hz, 2H), 6.64 – 6.58 (m, 1H), 6.56 (s, 4H), 6.47 (ddd, J = 8.1, 7.0,1.2 Hz, 2H), 3.35 (d, J = 1.7 Hz, 2H), 1.77 – 1.71 (m, 1H), 1.64 – 1.51 (m,2H), 1.42 (s, 1H), 1.25 (dd, J = 13.3, 5.8 Hz, 1H).

[0051] ④ The substrate is 4-methoxybenzaldehyde The corresponding product was 2,3-dihydro-2-(4-methoxyphenyl)-4(1H)-quinazolinone, with a yield of 95% and a purity of 97%; the NMR spectrum is shown below. Figure 8 As shown, its structural formula is as follows: ; 1 H NMR (500 MHz, DMSO- d 6) δ 7.93 (s, 1H), 7.60 – 7.45 (m, 6H), 6.73 –6.32 (m, 20H), 3.35 (d, J = 1.7 Hz, 10H), 1.87 – 0.93 (m, 12H).

[0052] ⑤ The substrate is 2-thiophene benzaldehyde The corresponding product was 2,3-dihydro-2-(2-thienyl)-4(1H)-quinazolinone, with a yield of 97% and a purity of 99%; the NMR spectrum is shown below. Figure 9 As shown, its structural formula is as follows: ; 1 H NMR (500 MHz, DMSO- d 6) δ 8.80 (s, 1H), 8.31 (s, 1H), 8.03 – 7.87(m, 2H), 7.77 (dd, J = 25.3, 3.3 Hz, 2H), 7.55 (td, J = 7.6, 1.6 Hz, 1H), 7.40 –7.21 (m, 3H).

[0053] Example 3 Similar to step (1) of Example 1, phosphomolybdic acid was replaced with molybdenum oxide in equal amounts, while other preparation conditions remained unchanged. The preparation method of the dihydroquinazolinone derivative in step (2) of Example 1 was adopted.

[0054] The yield of the product was 97%, and the purity was 98%.

[0055] Example 4 Similar to step (1) of Example 1, phosphomolybdic acid was replaced with silicomolybdic acid in equal amounts, while other preparation conditions remained unchanged. The preparation method of the dihydroquinazolinone derivative in step (2) of Example 1 was adopted.

[0056] The yield of the product was 95%, and the purity was 99%.

[0057] Example 5 Similar to step (1) of Example 1, phosphomolybdic acid was replaced in equal amounts with a molybdenum-containing oxygen cluster structure compound (such as cobalt-molybdic acid), while other preparation conditions remained unchanged. The preparation method of the dihydroquinazolinone derivative in step (2) of Example 1 was adopted.

[0058] The yield of the product was 96%, and the purity was 97%.

[0059] Comparative Example 1 Unlike Example 1, no catalyst was used (step (1) preparation of the catalyst was omitted), and the dihydroquinazolinone derivative was prepared according to step (2) of Example 1 (without adding a catalyst).

[0060] The yield of the product was 18%, and the purity was 64%.

[0061] Comparative Example 2 Unlike Example 1, the catalyst is TiO2, and it is prepared according to the preparation method of dihydroquinazolinone derivative in step (2) of Example 1 (catalyst is TiO2, 20 mg, without molybdenum-based components).

[0062] The yield of the product was 45%, and the purity was 58%.

[0063] Comparative Example 3 Unlike Example 1, the catalyst is phosphomolybdic acid, prepared according to step (2) of Example 1 for the preparation of dihydroquinazolinone derivatives (catalyst is phosphomolybdic acid, 20 mg, without TiO2).

[0064] The yield of the product was 50%, and the purity was 77%.

[0065] Comparative Example 4 Unlike Example 1, the catalyst in step (1) was prepared using a physical mixing (non-supported structure) method, that is, directly mixing TiO2 and PMA without any loading treatment. Specifically, 1.0 g of titanium dioxide (TiO2) was weighed and dispersed in 50 mL of deionized water, and ultrasonically dispersed for 30 min to prepare a TiO2 suspension. 0.10 g of phosphomolybdic acid (PMA) was weighed and dissolved in 10 mL of deionized water, and slowly added dropwise to the TiO2 suspension. The mixture was stirred at room temperature for 2 h to prepare a mixture. The resulting mixture was dried at 100 °C for 12 h, and then ground to obtain the composite catalyst.

[0066] Prepared according to step (2) of Example 1 (the catalyst is a physically mixed catalyst, 20 mg).

[0067] The yield of the product was 52%, and the purity was 74%.

[0068] Comparative Example 5 Unlike Example 1, step (2) omits the reaction under visible light LED (λ=420-450 nm) irradiation; instead, the raw material components are directly reacted under magnetic stirring at 25°C for 4 h. After the reaction is completed, the mixture is cooled, the catalyst is recovered by filtration, the solvent is evaporated under reduced pressure, and the target product is obtained by recrystallization with ethanol.

[0069] The yield of the product was 46%, and the purity was 59%.

[0070] As can be seen from the examples and comparative examples, the composite catalyst significantly improves the yield; the composite system is superior to the single component; and the reaction is further accelerated under light irradiation.

[0071] Example 6 This embodiment demonstrates the recyclability of the catalyst prepared in Example 1.

[0072] The catalyst used in step (2) of Example 1 for the preparation of dihydroquinazolinone derivatives was recycled and reused 5 times, yielding product yields of 95%, 94%, 93%, 93%, and 92%, respectively. This indicates that the catalyst has good stability.

[0073] (1) In the prior art, TiO2 is mainly used as a photocatalytic oxidation material. Its application in acid-catalyzed condensation cyclization reaction is rarely reported, and its catalytic activity is usually limited. (2) Although phosphomolybdic acid has acid catalytic activity, it has problems such as easy solubility, difficulty in recovery, and poor stability. (3) By constructing a semiconductor / molybdenum-based acidic composite structure, the present invention enables the two to form an interfacial synergistic effect, which not only maintains the acidic activity of the molybdenum-based component, but also improves the catalytic efficiency, catalytic selectivity and stability through semiconductor interface regulation.

[0074] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of a semiconductor / molybdenum-based acidic composite catalyst in the preparation of dihydroquinazolinone derivatives, characterized in that, The general structural formula of the dihydroquinazolinone derivative is as follows: ; wherein R is selected from alkyl, substituted alkyl, aryl and substituted aryl, wherein the substituent of the substituted alkyl or substituted aryl is selected from halogen, amino, alkoxy and thiophene. The semiconductor / molybdenum-based acidic composite catalyst includes a semiconductor material and a molybdenum-based acidic component loaded on its surface and inside, wherein the semiconductor material and the molybdenum-based acidic component form a heterojunction structure. The semiconductor material is selected from one or more of titanium dioxide, zinc oxide, zirconium oxide, aluminum oxide, tin oxide, and tungsten trioxide; The molybdenum-based acidic component is one or more of the following: ammonium molybdate, potassium molybdate, phosphomolybdic acid, silicomolybdic acid, molybdenum phosphopolyacid ammonium salt, molybdenum-containing oxygen cluster structure compound, molybdenum trioxide, and molybdenum dioxide. The semiconductor / molybdenum-based acidic composite catalyst exhibits photocatalytic activity under visible light with a wavelength of 420–450 nm. The preparation method of the semiconductor / molybdenum-based acidic composite catalyst includes the following steps: Semiconductor materials are added to a solvent to form a suspension, and molybdenum-based acidic components are added to the suspension and stirred until homogeneous. The reaction is carried out by hydrothermal method, and after the reaction is completed, the semiconductor / molybdenum-based acidic composite catalyst is obtained by drying.

2. The application of the semiconductor / molybdenum-based acidic composite catalyst according to claim 1 in the preparation of dihydroquinazolinone derivatives, characterized in that, The loading of the molybdenum-based acidic component is 1-30 wt%; The semiconductor material is titanium dioxide, and the molybdenum-based acidic component is phosphomolybdic acid.

3. The application of the semiconductor / molybdenum-based acidic composite catalyst according to claim 1 in the preparation of dihydroquinazolinone derivatives, characterized in that, The hydrothermal reaction temperature is 120–150℃, and the reaction time is 6–24 h.

4. The application of the semiconductor / molybdenum-based acidic composite catalyst according to claim 3 in the preparation of dihydroquinazolinone derivatives, characterized in that, The solvent is one or both of water and alcohol, and the mixing temperature is room temperature for 1-4 hours.

5. The application of the semiconductor / molybdenum-based acidic composite catalyst according to claim 3 in the preparation of dihydroquinazolinone derivatives, characterized in that, The drying temperature is 80–120°C, and the time is 6–12 h.

6. The application of the semiconductor / molybdenum-based acidic composite catalyst according to claim 1 in the preparation of dihydroquinazolinone derivatives, characterized in that, R is selected from halogen-substituted aryl, amino-substituted aryl, cycloalkyl, alkoxy-substituted aryl, and thiophene-substituted aryl, with the substitution position being the 4th or 6th position of the aryl group.

7. A method for preparing a dihydroquinazolinone derivative, characterized in that, In the presence of a semiconductor / molybdenum-based acidic composite catalyst in any of the applications described in claims 1-2, o-aminobenzamide undergoes a condensation cyclization reaction with aldehydes and ketones to obtain a dihydroquinazolinone derivative. The aldehydes and ketones include one or more of p-fluorobenzaldehyde, dimethylaminobenzaldehyde, p-nitrobenzaldehyde, cyclohexanone, 4-methoxybenzaldehyde, and 2-thiophenecarboxaldehyde.

8. The method for preparing the dihydroquinazolinone derivative according to claim 7, characterized in that, The condensation cyclization reaction was carried out under visible light irradiation at a wavelength of 420–450 nm and at 20–80 °C for 3–5 h.

9. The method for preparing the dihydroquinazolinone derivative according to claim 7, characterized in that, After the reaction is complete, the product is also subjected to concentration, extraction, drying and column chromatography.